ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KOMITMEN ORGANISASIONAL GURU - -, Sutarno - (Universitas Slamet Riyadi, 2006)
ABSTRACT The purposes of this research to know: 1) the effect of formal education level toward commitment organization, 2) the effect of during period job toward commitment organization, 3) the effect of salary toward commitment organization, 4) the effect with together between formal education level, during period job, and salary toward commitment organization, and 5) to know the one variabel give the effect toward commitment organization. This research is doing in the junior high school of SMP State Residence Sawit and Boyolali regency. The populations in this research are the all of teacher in the junior high school of SMP State Residence Sawit and Boyolali regency amount 121 teachers. The sample research take about 49,59% from populations amount 60 teachers with simple random sampling. The data analysis by using with multiple regressions, F-test, t-test and determinant coefficient (R2). According the data analysis with multiple regressions has result of corporation regression: Y = 13,382 + 1,572X1 + 1,183X2 + 4,294X3. The coefficient of formal education level is 1,572. The meaning of this matter is formal education level variable give effect toward to commitment organization is 1,572. The during period job variable have coefficient regression is 1,183, so the meaning of this matter is during period job variable give effect toward to commitment organization is 1,183. The salary variable have coefficient regression is 4,294, so the meaning of this matter is salary variable give effect toward to commitment organization is 4,294. Keywords: formal education level, during periode job, salary, commitment organization